2017
DOI: 10.1177/0261927x17718349
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Language Attitudes Toward Historically White Accents in the South African Context

Abstract: This study explores the use of Implicit Association Test as an effective research tool to investigate language attitudes in South Africa. We aim to show how Standard South African English and Afrikaans-accented English are cognitively managed by young L1 South African indigenous language speakers. Results corroborate (a) participants' statistically significant negative attitudes toward Afrikaans-accented English speakers, (b) the indexical nature of accents in triggering language attitudes, and (c) a main effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
(47 reference statements)
2
11
0
Order By: Relevance
“…According to the Associative -Propositional Evaluation model (Gawronski & Bodenhausen, 2006), IAT scores correspond to associate processes where previously existing information is automatically retrieved from memory. This aligns with the influence of home language on implicit attitudes understood as a result of past experiences and feelings (Álvarez-Mosquera & Marín-Gutiérrez, 2018). These findings are also consistent with previous research finding differences in explicit language attitudes depending on participants' home languages (Madariaga et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to the Associative -Propositional Evaluation model (Gawronski & Bodenhausen, 2006), IAT scores correspond to associate processes where previously existing information is automatically retrieved from memory. This aligns with the influence of home language on implicit attitudes understood as a result of past experiences and feelings (Álvarez-Mosquera & Marín-Gutiérrez, 2018). These findings are also consistent with previous research finding differences in explicit language attitudes depending on participants' home languages (Madariaga et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Focusing on languages as attitudinal objects,Redinger (2010) carried out a small-scale pilot study regarding language attitudes in Luxembourg. Along the same lines, Lee (2015) studied implicit attitudes towards Welsh and English in Wales and found differences between two educational contexts (i.e., Welsh-medium and English-medium schools) indicating preference for the language dominant in each context.The above studies showed that IAT has been used successfully with labels(Álvarez-Mosquera & Marín-Gutiérrez, 2018;Lee, 2015;McKenzie & Carrie, 2018) and audio stimuli(Álvarez-Mosquera & Marín-Gutiérrez, 2018;Lehnert & Hörstermann, 2018;Pantos & Perkins, 2012). However, Álvarez-Mosquera and Marín-Gutiérrez…”
mentioning
confidence: 97%
“…The IAT has also been used to assess prejudices against different varieties (Álvarez‐Mosquera, ; Pantos & Perkins, ; Redinger, ). For instance, Callesano and Carter () find no strong positive associations with Spanish in Miami using this test; Álvarez‐Mosquera and Marín‐Gutiérrez () find that South Africans whose L1 is an indigenous language had more negative associations with Afrikaans‐accented English than with Standard South African English. In adapted form, the IAT can measure the implicit associations of linguistic variables' social meaning and whether different variables correlate with each other (Campbell‐Kibler, ; Llamas, Watt, & MacFarlane, ), demonstrating that the test can be a useful tool for examining the processing of specific meaningful linguistic units.…”
Section: Methodologiesmentioning
confidence: 92%
“…The limitations of the IAT for sociolinguistic research have been pointed out by Campbell-Kibler (2013). The scarcity of acoustic IAT in the literature is also due to a methodological difficulty which is absent when working with visual material; acoustic stimuli, per se, stretch over time, while visual ones are perceived globally at once (Álvarez-Mosquera & Marín-Gutierrez, 2017). A key element to consider while interpreting the results is the methodological choice (due to the experimental design) of working with a binary category.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1960s, most research on language attitudes has been carried out by means of the matched and verbal guise technique (Giles & Powesland, 1975; Lambert, Hodgson, Gardner, & Fillenbaum, 1960) more recently, however, new indirect measures of attitudes have been developed in the field of social psychology and have been occasionally used by linguists, too, who crucially replaced visual stimuli (printed words, images) with audio stimuli in order to detect reactions to excerpts of speech and not to visual cues. While the so called “affective priming task” is employed by Speelman, Spruyt, Impe, and Geeraerts (2013), the research carried out by Álvarez-Mosquera and Marín-Gutiérrez (2017), Pantos and Perkins (2012), and Roessel, Schoel, and Stahlberg (2018) represents an expansion of the Implicit Association Test (IAT) methodology, which was originally developed by Greenwald, McGhee, and Schwartz (1998) in the field of social psychology. In an IAT participants do not consciously filter their answers since they are asked to sort stimuli into concept categories and make immediate associations.…”
Section: Explicit and Implicit Attitudes Toward Accentsmentioning
confidence: 99%